CURRENT ISSUES OF RESTRICTION OF A PERSON’S PERSONAL FREEDOM IN THE APPLICATION OF PENALTY TO IT AND SOME OTHER RELATED MEASURES OF CRIMINAL RIGHTS - Лихова, Софія Яківна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Review of the monograph by K.A. Novikova "Restriction of liberty as a form of punishment". The reviewer notes that given the legal and practical importance of the institution of restriction of the human right to freedom, the need to minimize the abuse of restrictions on human freedom, this issue needs scientific and theoretical understanding. The peer-reviewed monograph is a significant contribution to solving complex theoretical and applied problems of criminal law of Ukraine. Theoretical substantiations, conclusions and offers are of considerable interest both for legal science, and for practical activity of judicial bodies.